Perbedaan Harga Diri Pada Remaja Korban Cyberbullying Ditinjau Dari Jenis Kelamin : Sandra Adetya, Yomima Viena, Althof Wahyu Pradana - Adetya, Sandra; Viena, Yomima; Wahyu Pradana , Althof (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
The development of technology and communication in the midst of globalization is something that cannot be denied for all people in Indonesia, especially for teenagers, the use of social media allows teenagers to be able to connect with everyone without space and time restrictions, besides that social media can also be used as a forum for In learning, apart from having many positive impacts, the use of social media also has many negative impacts, one of which is cyberbullying behavior. Many teenagers are victims of cyberbullying behavior, thus affecting the victim's daily life, and the victim's selfesteem. The subjects used in this study were teenagers, aged 11-21 years, domiciled in the Penggilingan Village, East Jakarta. The results of the categorization test found that women are better at handling cases of self-esteem, and the majority of adolescents who have been or are currently victims of cyberbullying have a good level of self-esteem.